Permasalahan Sengketa Kepemilikan dengan Alas Hak Surat Keterangan Riwayat Tanah (SKT) Serta Akibat Bagi Pemegangnya - Helena Albright Sitompul (UNES Law Review, 2023)
This article discusses the position of a Land History Certificate or "SKT", when used as proof of ownership of a plot of land in general or when litigating in court. The purpose of this writing is to provide education regarding the existence of SKT which is used as proof of land ownership and its position at the level of land law in Indonesia. The results of the research are that a certificate is the highest proof of control and ownership of land, so that normatively there is no single piece of evidence, including SKT, which can replace the position of a certificate in the context of proving land rights. However, the process of obtaining a certificate is not easy, which is an obstacle, so there is still a lot of land that has not been certified. The assumption that SKT is strong evidence is still often found in society. This perspective results in the land certification process becoming less important and having a certificate is not a necessity. SKT is considered capable of providing a sense of security for its holders. For SKT holders, by referring to the mixed publication system adopted in the land registration regulations, in terms of evidence, it is possible for the SKT to become proof of land ownership. The negative publication system with positive elements means that the Certificate is strong evidence, but not absolute, so that anyone who feels most entitled as the holder of land rights, should be able to prove themselves with the evidence they hold.